2022
DOI: 10.3390/foods11060858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tea Powder on the Cooking Properties, Antioxidative Potential and Volatile Profiles of Dried Noodles

Abstract: Numerous studies indicate that tea has versatile health benefits, and attempts are being made to use it as a food additive. In this study, three types of tea powder (TP) [matcha tea powder (MTP), green tea powder (GTP), and black tea powder (BTP)] were used in noodle processing, and the cooking properties, antioxidant potential, and volatile profiles of dried tea noodles (DTN) were investigated. Between 0.5% and 2% TP addition decreased the cooking time, cooking loss, and water absorption of DTN, regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Additionally, green tea was also added to the dough mixture instead of water to prevent the fats from oxidation during their shelf‐life. The addition of green tea to the noodle formulation has been proposed by several studies to improve the overall nutrients of the product and benefit from its antioxidant qualities (Kayama et al., 2022 ; Xu et al., 2019 , 2023 ; Yu et al., 2019 , 2020 ). Green tea contains an amino acid called L‐theanine, which has been shown to promote relaxation and reduce stress (Williams et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, green tea was also added to the dough mixture instead of water to prevent the fats from oxidation during their shelf‐life. The addition of green tea to the noodle formulation has been proposed by several studies to improve the overall nutrients of the product and benefit from its antioxidant qualities (Kayama et al., 2022 ; Xu et al., 2019 , 2023 ; Yu et al., 2019 , 2020 ). Green tea contains an amino acid called L‐theanine, which has been shown to promote relaxation and reduce stress (Williams et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafine tea powder is a natural food colorant that affects the sensory quality of bakery products in terms of color and taste and increases their popularity and nutritional value (Wang, Tu, et al., 2021). In terms of food processing properties (e.g., viscosity, thermodynamics, and rheology), the addition of ultrafine tea powder improves color, cooking quality, texture, and flavor and enhances antioxidant and antimicrobial abilities (Kayama et al., 2022; Xu et al., 2019). Attention should be paid to the additional amount.…”
Section: Value‐added Utilization Of Pruned Tea Biomass In the Food In...mentioning
confidence: 99%
“…Kayama et al [44] found that the addition of green tea powder significantly increased the values of phenolic compounds in fresh pasta. This behavior corroborates the data found in the present work.…”
Section: Colorimetric Analysis Pigments and Bioactive Compoundsmentioning
confidence: 99%
“…Such behavior can result in palm flour being a good additive in the enrichment of fresh pasta. In addition to having antioxidant, anticancer, anti-inflammatory, and vasodilator effects, phenolic compounds are associated with the prevention of various diseases [44].…”
Section: Colorimetric Analysis Pigments and Bioactive Compoundsmentioning
confidence: 99%